Recent progress in paleontological methods for dating the Tree of Life - Laurin, Michel (Frontiers in Genetics, 2012)
Dating the Tree of Life (abbreviated TOL below) has become a major goal of biological research. Beyond the intrinsic interest of reconstructing the history of taxonomic diversification, time-calibrated trees (timetrees for short, as used throughout below) are required in many types of comparative analyses, where branch lengths are used to assess the conservation importance of lineages, correlation between characters, or to assess phylogenetic niche conservatism, among other uses. Improvements in dating the TOL would thus benefit large segments of the biological community, ranging from conservation biology and ecology through functional biology and paleontology. Recently, progress has been made on several fronts: in compiling databases and supertrees incorporating paleontological data, in computing confidence intervals on the true stratigraphic range of taxa, and in using birth and death processes to assess the probability distribution of the time of origin of specified taxa. Combined paleontological and molecular dating has also progressed through the insertion of extinct taxa into data matrices, which allows incorporation of their phylogenetic uncertainty into the dating analysis.